Non-immune Cell Components in the Gastrointestinal Tumor Microenvironment Influencing Tumor Immunotherapy - Li, Zhengshuo; Zhang, Xiaoyue; Liu, Can; Ma, Jian (Frontiers in Cell and Developmental Biology, 2021)
Interactions of genetic susceptibility factors, immune microenvironment, and microbial factors contribute to gastrointestinal tumorigenesis. The suppressive immune microenvironment reshaped by the tumors during gastrointestinal tumorigenesis directly contributes to T-cell depletion in tumor immunotherapy. Soluble factors secreted by tumor cells or stromal cells collectively shape the suppressive immune environment. Here, we reviewed the key factors in the gastrointestinal tumor microenvironment that influence tumor immunotherapy, focusing on the effects of fibroblasts, neuronal cells, soluble cytokines, exosomes, and the microbiome in tumor microenvironment. Research in this field has helped to identify more precise and effective biomarkers and therapeutic targets in the era of tumor immunotherapy.